Revitalisasi Hubungan China-India Melalui Peran Shanghai Cooperation Organization (SCO) : Perspektif Konstruktivisme - Fetra Ardianto (Jurnal Alternatif - Jurnal Ilmu Hubungan Internasional, 2023)
China and India were born as two economic giants which cooperate with each other in an economic association known as BRICS. However, the rivalry between the two countries is inevitable and continues, especially in the border areas. Seeing these conditions, China and Russia are trying to invite India to join as a permanent member of the Shanghai Cooperations Organization (SCO). The invitation received a positive response from the Indian side, where on 9 June 2017 India officially joined as a permanent member of the SCO. This study focuses on the role of SCO in efforts to revitalize relations between China and India. In general, it can be concluded that there are two roles performed by the SCO in an effort to revitalize relations between the two countries, namely through cooperation in the security and economic fields. In particular, by using the constructivism perspective, it can be understood that in this case the SCO acts as a form of collective identity and as a form of behavioral standards or norms. The formation of a collective identity carried out by the SCO, in this case serves to direct the relations between China and India into a strong bond of friendship. In addition, with the norms or standards of behavior established by the SCO, China and India in this case will certainly try to restrain themselves from conflict with each other because of the bonds of these norms that must be obeyed by each SCO member country.